1996
DOI: 10.1590/s0004-282x1996000400012
|View full text |Cite
|
Sign up to set email alerts
|

The hyperactive child and the body: a clinical study on the origin of hyperactivity in children

Abstract: -A group of 22 hyperactive children from 7 to 12 years of age was selected among 38 out-patients registered at Hospital do Servidor Público de São Paulo (Civil Servant Hospital of the State of São Paulo). Their psychiatric evaluation was negative, the neurological examination showed "psychomotor syndrome", and psychological evaluation revealed disorders related with Ego maturation in all cases. Although all children were referred to psychotherapy, only thirteen underwent individual sessions once a week for an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Quasi-experimental studies: three studies employed quasi-randomised methods of assignment to each treatment arm: -Psychoanalytic child psychotherapy (alongside in-patient medical care) vs in-patient medical care only for children with dangerously uncontrolled diabetes (Moran and Fonagy, 1987;Fonagy and Moran, 1990;Moran et al, 1991) -Brief, focused psychodynamic psychotherapy vs assessment only for children with emotional disorders (Muratori et al, 2002(Muratori et al, , 2003(Muratori et al, , 2005) -Short-term psychodynamic psychotherapy vs waiting list control for children and adolescents with a range of disorders Kronmu¨ller et al, 2010) Level 3. Controlled observational studies: eight controlled observational studies were identified, using a range of control groups, including no-treatment control groups, non-matched control groups or the matching of the comparison group on the basis of clinical and demographic characteristics: -Intensive (four times weekly) psychoanalytic child psychotherapy vs once weekly psychoanalytic child psychotherapy for children with learning difficulties and emotional disturbance (Heinicke, 1965;Heinicke and Ramsay-Klee, 1986) -Psychodynamically orientated therapy vs supportive educational therapy for adolescents with OCD (Apter et al, 1984) -Psychoanalytic child psychotherapy vs no treatment control group for adopted children with 'severe difficulties' (Lush et al, 1991;Boston and Lush, 1994;Lush et al, 1998;Boston et al, 2009) -Individual psychotherapy vs untreated control group attending hospital for children with 'hyperactivity and attention deficit' (Jordy and Gorodscy, 1996) -Long-term follow-up of psychoanalytic child psychotherapy vs no treatment control group (Midgley and Target, 2005;Midgley et al, 2006;Schachter and Target, 2009) -Long-term psychodynamic psychotherapy for adolescents with a range of disorders vs It should be kept in mind that a study's position in this 'hierarchy of evidence' does not necessarily reflect the quality of the study. There is a great deal of debate about the assumptions built into the idea of a 'hierarchy of evidence' and especially the emphasis placed on randomised controlled trials (RCTs) as the 'gold standard' for psychotherapy research (see, for example, Leichsenring, 2004;Wachtel, 2010).…”
Section: Findings Of the Reviewmentioning
confidence: 99%
“…Quasi-experimental studies: three studies employed quasi-randomised methods of assignment to each treatment arm: -Psychoanalytic child psychotherapy (alongside in-patient medical care) vs in-patient medical care only for children with dangerously uncontrolled diabetes (Moran and Fonagy, 1987;Fonagy and Moran, 1990;Moran et al, 1991) -Brief, focused psychodynamic psychotherapy vs assessment only for children with emotional disorders (Muratori et al, 2002(Muratori et al, , 2003(Muratori et al, , 2005) -Short-term psychodynamic psychotherapy vs waiting list control for children and adolescents with a range of disorders Kronmu¨ller et al, 2010) Level 3. Controlled observational studies: eight controlled observational studies were identified, using a range of control groups, including no-treatment control groups, non-matched control groups or the matching of the comparison group on the basis of clinical and demographic characteristics: -Intensive (four times weekly) psychoanalytic child psychotherapy vs once weekly psychoanalytic child psychotherapy for children with learning difficulties and emotional disturbance (Heinicke, 1965;Heinicke and Ramsay-Klee, 1986) -Psychodynamically orientated therapy vs supportive educational therapy for adolescents with OCD (Apter et al, 1984) -Psychoanalytic child psychotherapy vs no treatment control group for adopted children with 'severe difficulties' (Lush et al, 1991;Boston and Lush, 1994;Lush et al, 1998;Boston et al, 2009) -Individual psychotherapy vs untreated control group attending hospital for children with 'hyperactivity and attention deficit' (Jordy and Gorodscy, 1996) -Long-term follow-up of psychoanalytic child psychotherapy vs no treatment control group (Midgley and Target, 2005;Midgley et al, 2006;Schachter and Target, 2009) -Long-term psychodynamic psychotherapy for adolescents with a range of disorders vs It should be kept in mind that a study's position in this 'hierarchy of evidence' does not necessarily reflect the quality of the study. There is a great deal of debate about the assumptions built into the idea of a 'hierarchy of evidence' and especially the emphasis placed on randomised controlled trials (RCTs) as the 'gold standard' for psychotherapy research (see, for example, Leichsenring, 2004;Wachtel, 2010).…”
Section: Findings Of the Reviewmentioning
confidence: 99%
“…One study focused on children and young people specifically diagnosed with CD (Edginton et al, 2018), and one focused on children diagnosed with ODD (Prout et al, 2019). One study of hyperactive children was too poorly designed to draw conclusions (Jordy and Gorodscy, 1996). In addition to these studies, two papers have reported secondary analyses of larger studies of mixed populations, with the secondary analyses focusing on outcomes for those children with a range of externalizing disorders (Fonagy and Target, 1994;Winkelmann et al, 2000).…”
Section: Behavioral Disordersmentioning
confidence: 99%